Effect of different coloured shade nets on production and quality of cordyline - GAURAV, ABHAY KUMAR; RAJU, D V S; JANAKIRAM, T; SINGH, BHUPINDER; JAIN, RITU; KRISHNAN, S GOPALA (The Indian Journal of Agricultural Sciences, 2016)
Cordyline terminalis is an important ornamental plant used for its beautiful foliage as cut green. This plant prefers shade for optimum growth. The effect of different coloured shade nets (red, green, black, and white with 50% shading intensity) along with control (without shade net) on production and quality of Cordyline terminalis was studied. The effect of spectral control of light on physiology and vegetative development was evaluated at different crop growth stages. The results showed that plants grown under shade nets produce good quality foliage and biomass irrespective of colour. The cut greens grown under red and white shade nets were exposed to higher PAR and transmittance than other colour nets and hence had better performance in terms of plant height, number of leaves, biomass, leaf area, photosynthetic rate, harvest index compared to control. Vase life of the foliage was higher under coloured shade nets when compared to open condition but significance difference was not found between different colours. White and red shade nets were found to be best for growing cordyline.